Promoting Intellectual Property Propaganda Activities in Vocational Education Institutions: An Assessment from a Management Perspective - AnLong DangNguyen (Randwick International of Education and Linguistics Science Journal, 2024)
Along with the comprehensive innovation of Vietnam’s education system, vocational education is positively changing, making great contributions to the country’s education system. Along with the university education system, vocational education is considered a place to create new knowledge and technology; but up to now, the number of applications to establish protection of industrial property rights, especially inventions, still accounts for a low rate; the understanding of education and training staff in vocational education institutions (VEIs) about intellectual property rights is not high. Based on the study of state legal documents on intellectual property rights, this article surveyed 300 people who are managers, teachers, students, and pupils at several educational institutions in Ho Chi Minh City through surveys and interview questions. VEIs do not pay much attention to intellectual property activities in general and intellectual property propaganda activities in particular; there is no long-term plan and policy for implementing intellectual property activities and intellectual property propaganda at VEIs. Based on that reality, and an assessment of the current situation combined with state legal documents, this article proposes some management solutions to promote intellectual property activities and intellectual property propaganda activities in VEIs in near the future.